Revision of the Seashore-dwelling Subgenera Emplenota Casey and Triochara Bernhauer (Coleoptera: Staphylinidae: genus Aleochara) from Japan - Yamamoto, Shûhei; Maruyama, Munetoshi (Zootaxa, 2012)
The Japanese species of the seashore-dwelling subgenera Emplenota Casey and Triochara Bernhauer of the genus Aleochara Gravenhorst are revised. Five species are recognised in Emplenota, of which three are described as new species: Aleochara (Emplenota) segregata n. sp., A. (E.) hayamai n. sp. and A. (E.) yamato n. sp. The remaining known species A. (E.) fucicola Sharp and A. (E.) puetzi (Assing) are redescribed. Three species recognised in Triochara, Aleochara (Triochara) trisulcata Weise, A. (T.) zerchei (Assing) and A. (T.) nubis (Assing) are redescribed. All species are keyed. For some species ecological data are reported. The phylogenetic relationships of the Japanese species are discussed, and the distributions of all species are mapped.